GAGASAN BAIT SUCI DALAM KITAB WAHYU - H. Pidyarto (Studia Philosophica et Theologica, 2004)
The Revelation of John, the last book of the New Testament, expresses the Church’s eschatological hope, i.e. the hope for the final victory of God over Satan at the end of all ages. That hope is proclaimed and celebrated first of all when the faithful come together for worship. That is why the Revelation of John is full of symbolism taken from liturgy, such as reading, listening, blessing, doxology, lampstand, incense, and temple. This article shows how the symbolism of temple (Greek: naos) is used in that book. Before the consummation of the world becomes a reality, so many things should first take place on earth. It is from his throne in heavenly temple that God controlls the world. Besides, on one hand the final state of the faithful is depicted as becoming a permanent part of the heavenly temple (Rev 3:12), but on the other hand it is described as living in the New Jerusalem which in its turn is depicted as a perfect city but also as a huge and perfect temple, resembling the Holy of the Holies of the temple in earthly Jerusalem (Rev 21:16). That is why there will be no temple any longer in that city (Rev 21:22).